2015
DOI: 10.1080/01919512.2014.998756
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Ozone Decay in Homogeneous Phosphate-Buffered Medium

Abstract: The ozone decomposition reaction is analyzed in a homogeneous reactor through in-situ measurement of the ozone depletion. The experiments were carried out at pHs between 1 to 11 in H 2 PO 4 − /HPO 4 2-buffers at constant ionic strength (0.1 M) and between 5 and 35 • C. A kinetic model for ozone decomposition is proposed considering the existence of two chemical subsystems, one accounting for direct ozone decomposition leading to hydrogen peroxide and the second one accounting for the reaction between the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Some researchers indicated that phosphate ions inhibit ozone decomposition 33 36 , while others revealed that phosphate species accelerate ozone decomposition 34 , 37 . The latter effect was found to be the most pronounced at low pH 38 . In 1985, Staehelln and Hoigne 34 established that phosphate ions do not react with ozone; however, they can react with HO • radicals.…”
Section: Resultsmentioning
confidence: 85%
“…Some researchers indicated that phosphate ions inhibit ozone decomposition 33 36 , while others revealed that phosphate species accelerate ozone decomposition 34 , 37 . The latter effect was found to be the most pronounced at low pH 38 . In 1985, Staehelln and Hoigne 34 established that phosphate ions do not react with ozone; however, they can react with HO • radicals.…”
Section: Resultsmentioning
confidence: 85%
“…Conventional ozonation and heterogeneous catalytic ozonation (HCO) processes have been widely used for drinking water and wastewater treatment due to their relatively low capital cost, low energy demand, and regulated formation of disinfection by-products. The degradation of organic compounds during conventional ozonation and HCO mostly occurs as a result of interaction with O 3 and/or other oxidants (particularly hydroxyl radicals, • OH) generated on O 3 decay. The overall process efficiency is highly dependent on pH due to the influence of pH on O 3 self-decay kinetics, surface charge of the catalysts, and organic speciation. Research on the ozonation and HCO processes is commonly performed under circumneutral pH conditions (i.e., pH 6.5–8.5) with the pH typically controlled using phosphate- and/or carbonate-buffered solution. While carbonate, the major buffer in natural waters and many wastewaters, ,, is recognized to stabilize O 3 by scavenging • OH and inhibiting radical chain reactions, , there are contradictory reports on the influence of phosphate ions on O 3 decay. Some studies suggest that the addition of phosphate decreased the rate of O 3 decay by scavenging • OH and inhibiting radical chain reactions in a manner similar to carbonate while others observed promotion of O 3 decay. ,, The use of phosphate buffers may also have a significant impact on the surface chemistry of catalysts and efficacy of HCO with regard to organic removal since phosphate is a strong Lewis base that adsorbs on the surface of catalysts, thereby inhibiting catalyst–O 3 interaction and/or organic sorption on the catalyst surface. While most studies report a decrease in organic oxidation during HCO in the presence of phosphate ions due to inhibition of the interaction of O 3 and/or organics with the catalyst as a result of phosphate sorption on surface hydroxyl sites, …”
Section: Introductionmentioning
confidence: 99%
“…31−34 Some studies suggest that the addition of phosphate decreased the rate of O 3 decay by scavenging • OH and inhibiting radical chain reactions in a manner similar to carbonate 33 while others observed promotion of O 3 decay. 31,32,34 The use of phosphate buffers may also have a significant impact on the surface chemistry of catalysts and efficacy of HCO with regard to organic removal since phosphate is a strong Lewis base that adsorbs on the surface of catalysts, thereby inhibiting catalyst−O 3 interaction 35−37 sorption on the catalyst surface. 37−42 While most studies report a decrease in organic oxidation during HCO in the presence of phosphate ions due to inhibition of the interaction of O 3 and/or organics with the catalyst as a result of phosphate sorption on surface hydroxyl sites, 43−50 some contrasting results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For phosphate ions (i.e., H 2 PO 4 − and HPO 4 2− at pH 6∼8), both promotion and inhibition of these chain reactions have been proposed in the literature. It was suggested that H 2 PO 4 − might participate as a proton source for the formation of ozonide radical HO 3 •, 43,44 which is then converted to •OH and reacts with O 3 . 45 On the other hand, phosphates are also considered as •OH scavengers and thus may inhibit ozone decomposition.…”
Section: Effects Of Water Matrices Onmentioning
confidence: 99%